Determination of shear surface of landslides using electrical resistivity tomography - DOSTÁL, Ivan; PUTIŠKA, René; KUŠNIRÁK, David (Contributions to Geophysics and Geodesy, 2014)
Geophysical methods offer a broad spectrum of information by dealing with slope deformations. The electrical resistivity tomography (ERT) method is mainly applied for spatial localization of the landslide body and depicting the shear zone position. This article presents the application of the ERT method for the landslide hazardous areas by means of numerical modelling. Four different synthetic models with very small resistivity contrast (30 Ohm.m/50 Ohm.m), where each model represents a different type of slope deformation, were tested by several factors affecting the final inverse model: measurement point density, L1 and L2 norm and L-norm roughness filter components. The higher measurement points density helps mainly to detect the boundaries at greater depths. Inverse models computed using the L1 norm bring satisfactory results for compact anomalous bodies, i.e. water saturated landslide body. In the case of subtle conductive zones, i.e. shear planes, the L2 norm based inversion is recommended. For enhanced reconstruction of skewed anomalous objects, roughness filter including a diagonal component produces more accurate inverse image. The article also demonstrates the ability of the ERT method to detect and describe the shape of the slope deformation even by a relative subtle resistivity contrast.